Superfauna and superheroes: Re-imagining New Zealand and the Pacific in the impossible worlds of comic books. Issue 1 (1st May 2019) - Conrich, Ian
Visual culture has repeatedly been associated with exercises in mythmaking, with consumers fed images that prioritize an appeal to their aesthetic sensibilities and their demands for the sensational, sublime, unfamiliar and the fantastic. Film, computer games and comic books are especially fertile grounds for mythmaking with the primary sources of production – the United States, Japan and Europe – re-imagining and re-presenting foreign cultures to the point that many are transformed into impossible worlds. Key characteristics of a foreign culture can become representative of a national identity, and these are often heightened and exaggerated. Within the Pacific, South Seas myths have been effective in helping to convey an abundance of stories of adventure and romance, yet there have been only sporadic attempts to understand the microcosmic ways in which mythmaking functions regionally. Moving beyond studies of popular culture depictions of Hawai'i and Rapanui, this article considers the representations in American comic books of animals of the Pacific and, in particular, New Zealand. The focus here is on lands of unfamiliar creatures where the animals have acquired special powers and become superfauna.